Making Up Mathematical Problems - Munisa Aminovna Davlatova (Academia One Publishing, 2023)
The article presents the main stages of make up mathematical problems. Three foundations of making problems are described: the form, the contents and the solution of the problem. The analyzed material gives evidence that pupils’ making up mathematical problems is a tool for developing universal practical operations in maths class.
Keywords: universal practical operations; stages of make up problems; the type and the structure of the problem.